Bacterioplankton production in freshwater Antarctic lakes - Laybourn-Parry, J; Henshaw, T; Jones, DJ; Quayle, W (Freshwater Biology, 2004)
1. Bacterioplankton production was measured in the water columns of two ultraoligotrophic,freshwater Antarctic lakes (Crooked Lake and Lake Druzhby) during an annualcycle. In both lakes bacterial production, measured by the incorporation of [3H] thymidine,continued in winter and showed a cycle over the year. The range of production was between 0and 479 ng C L)1 h)1 in Crooked Lake and 0354 ng L)1 h)1 in Lake Druzhby.2. Abundance and mean cell volume both varied, producing marked changes in biomassduring the year, with highest biomass occurring in the winter and early spring. Biomassshowed similar seasonal trends in both lakes.3. For most of the year inorganic forms of nitrogen and phosphorus were detectable in thewater columns of the lakes and were unlikely to have limited bacterial production.Dissolved organic carbon (DOC) was below 3000 lg L)1. Dissolved amino acids andcarbohydrates contributed 525% of the DOC pool in Crooked Lake and 564% in LakeDruzhby. Dissolved carbohydrates were consistently low, suggesting that this may havebeen the preferred carbon substrate for bacterioplankton.4. Aggregate associated bacteria had higher mean cell volume, abundances and productionthan freely suspended bacteria in Lake Druzhby, while in Crooked Lake aggregateassociated bacteria consistently had higher mean cell volumes than free bacteria, butabundance and production were on occasion higher in free bacteria compared withaggregate associated communities.5. The data indicated that production is limited by continuous low temperatures and thelimited availability of suitable DOC substrate. However, the bacterioplankton functionsyear round, responding to factors other than temperature.